Mononeuritis multiplex in a patient with macroglobulinaemia. Issue 7 (July 1976) - Fraser, D M; Parker, A C; Amer, S; Campbell, I W
Abstract : A case is described of a 73 year old male with Waldenström's macroglobulinaemia and hyperviscosity in association with neurological abnormalities, the Bing-Neel syndrome. The relationship of the clinical features to changes in serum viscosity and the response to therapy with plasmapheresis and chlorambucil are discussed.